A framework for undergraduate research in economics. (21st July 2015) - Wagner, Jeffrey
<x xml:space="preserve">Abstract</x> The purpose of this article is to propose a framework to facilitate the achievement of greater economies of scope in economics research and undergraduate teaching. A four‐year research plan is proposed, followed by discussion of practical strategies for overcoming barriers to undergraduate research in economics. Emphasis is placed on (i) bringing undergraduates into research programs as soon as the first semester and (ii) encouraging and incentivizing faculty members to participate in undergraduate research initiatives.